transforme os itens dados em uma so potencia.
a) (√2)^4.(√2)^-8
b) (√2)^-7 : (√2)^-9
Soluções para a tarefa
Respondido por
112
a) ![( \sqrt{2} )^4*( \sqrt{2})^-^8 = (\sqrt{2})^4^+^(^-^8^) = ( \sqrt{2})^-^4 ( \sqrt{2} )^4*( \sqrt{2})^-^8 = (\sqrt{2})^4^+^(^-^8^) = ( \sqrt{2})^-^4](https://tex.z-dn.net/?f=%28+%5Csqrt%7B2%7D+%29%5E4%2A%28+%5Csqrt%7B2%7D%29%5E-%5E8+%3D++%28%5Csqrt%7B2%7D%29%5E4%5E%2B%5E%28%5E-%5E8%5E%29+%3D+%28+%5Csqrt%7B2%7D%29%5E-%5E4++++)
b)
b)
Divisao49:
nao consigo entender, e agora?
Perguntas interessantes
Física,
1 ano atrás
Matemática,
1 ano atrás
Filosofia,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás